Study on rotational effects of modern turbine blade on coolant injecting nozzle position with film cooling and vortex composite performance - Wang, Jiefeng (2024)
The flow structure of the vortex cooling is asymmetrical compared to the traditional gas turbine leading edge cooling, such as the impingement cooling and the axial f low cooling. This asymmetrical property will affect the cooling performance in the blade leading edge, whereas such effects are not found in most of the studies on vortex cooling due to the neglect of the mainstream f low in the airfoil channel. This study involves the mainstream f low field and the rotational effects based on the profile of the GE E3 blade to reveal the mechanism of the asymmetrical f low structure effects. The nozzle position on the characteristics of the vortex and film composite cooling in the turbine rotating blade leading edge is numerically investigated. The cool-ant injecting nozzles are set at the side of the pressure surface (PS-side-in) vs. that is set at the side of the suction surface (SS-side-in) to compare the cooling characteristics at the rotating speed range of 0–4000 rpm with f luid and thermal conjugate approach. Results show that the nozzle position presents different inf luences under low and higher rotational speeds. As for the mainstream f low, rotation makes the stagnation line move from the pressure surface side to the suction surface side, which changes the coolant film attachment on the blade leading edge surface. The position of nozzles, however, indicates limited inf luence on the coolant film f low. As for the internal channel vortex f low characteristics, the coolant injected from the nozzles forms a high-velocity region near the target wall, which brings about enhancing convective heat transfer. The f low direction of the vortex f low near the internal channel wall is opposite and aligns with the direction of Coriolis force in both the PS-side-in and SS-side-in, respectively. Therefore, the Coriolis force augments the convective heat transfer intensity of the vortex cooling in the internal channel in SS-side-in while weakening the internal heat transfer in PS-side-in. Such effects become more intense with higher rotational speed. The blade surface temperature decreases as the Coriolis force increases the internal heat transfer intensity. The SS-side-in suggests a superior composite cooling performance under the relatively higher rotating speed. The SS-side-in structure is recommended in the gas turbine blade leading edge running at a higher rotating speed.